First Case of Tularemia Reported in Portugal: Probably of Imported Origin - Lopes de Carvalho, Isabel; Nascimento, Paula; Núncio, Maria Sofia; Toscano Rico, Miguel (Frontiers in Public Health, 2018)
The authors report the case of a 47-year-old man who walked in the countryside on the island of Bornholm, during the summer period. Three days later, a fever, myalgias and adynamia began. The serological tests, PCR and isolation of the bacteria confirmed the presence of Francisella tularensis subsp. holarctica infection.